Countermovement Jump with the Help of Wings in 16-Year-Old Volleyball Players - Pogoni, Junida; Pogoni, Artan (European Journal of Multidisciplinary Studies, 2021)
Vertical jump is combined with the assessment of the strength and strength of the muscles of the lower extremities that are fundamental components of the volleyball game’s work.The Countermovement Jump with arm (CMJA) test as a specific specifically for the assessment of the offensive force of volleyball players.Methods: Female (F) - Males (M) average volleyball players were tested in CMJA at the GFRP; Force(F max), Power(P max) and gravity shift relationship Jump Height(JH). Anthropometric measurements of volleyball players were also developed; Body Height (BH cm), Body Mass (BMI% kg/m²), Body Weight (BW kg). Results: The differences between the two groups found in the study resulted in significant differences in BH cm (F-172, M-187.3), BW kg (F- 62.2, M -79.3), BMI kg / m² (F-21.1, M -22.6), Jump place in JP cm (F-266, M-310), Jump Attack in JA cm (F-274, M-321). But even the data captured by the Leonardo platform in the CMJA test gives us a noticeable difference between the two groups; (F-6.4,M-4.5), P max (F-3.08, M-4.78) and diff P max Left - Right(F-2.59,M-0.56),V max m/%(F-5.2,M-4.4). Conclusion: The results obtained suggest changes to the performance of volleyball players in "vertical jump" in the parameters of force, speed, and power. These indicators are valid for any trainer or volleyball player to implement a detailed and specific training program for the further development of the physical qualities of volleyball players, especially vertical tipping in gaining the lower extremity muscular power.